KOMUNIKASI INTERPERSONAL BARISTA PEREMPUAN DALAM MELAWAN FRAMING NEGATIF KHALAYAK - Hanifah Nurdin; Azman (AT-TANZIR: JURNAL ILMIAH PRODI KOMUNIKASI PENYIARAN ISLAM, 2022)
In Banda Aceh, the proliferation of modern, unique coffeeshops and coffee variants has made female baristas appear. The profession as a barista which was originally performed by men has been loved by women. Female baristas have worked in several coffeeshops. In terms of service, knowledge and responses from customers stated that female baristas were often considered incompetent, not smart, less thorough in serving coffee, and often received negative framing from the audience. This research was conducted to answer how the interpersonal communication built by female baristas in dealing with negative framing from the audience. The research method uses qualitative research with descriptive writing. Data obtained by conducting observations, interviews and documentation. From the research, it was found that negative framing can be countered with five attitudes which are important values ​​in interpersonal communication. The five attitudes are, empathy, support, positive attitude, and other information. In addition, baristas never stop learning to develop themselves, values ​​and rules and behaviors that can make customers feel comfortable and return to the coffee shop. Thus, with an open attitude, polite speech, good service and attractive appearance, female baristas can accept attendance.